Mediating effects of general self‐efficacy on social support and quality of life in patients after surgical aortic valve replacement - Xuecui Zhang; Xizhen Huang; Yanchun Peng; Long Huang; Lingyu Lin; Liangwan Chen; Yanjuan Lin (Wiley, 2023)
Abstract Aim To explore whether general self‐efficacy can mediate the relationship between social support and quality of life in patients after surgical aortic valve replacement. Design A cross‐sectional design. Methods The final analysis included 283 patients who underwent surgical aortic valve replacement from May 2021 to September 2021. They completed a set of questionnaires, including the Chinese version of the General Self‐Efficacy Scale, the Chinese Questionnaire of Quality of life in Patients with Cardiovascular Diseases and the Social Support Rating Scale. The PROCESS Macro in SPSS was used to analyse the mediating effect. Results Quality of life and all of its dimensions were significantly related to social support and general self‐efficacy. A significant indirect effect of social support existed through general self‐efficacy in relation to quality of life with the mediation effect ratio of 32.82%.